A new species of Charissa Curtis, 1826 from Europe (Lepidoptera: Geometridae) - Erlacher, Sven; Erlacher, Josepha (Zootaxa, 2017)
Charissa is a species-rich genus within the geometrid subfamily Ennominae, and is widely distributed in the Palaearctic and the Oriental regions; one species also occurs in the Nearctic. Their perfect adaptation to rocks on which they rest during daytime makes them sometimes difficult to tell apart on habitus. For that it is often necessary to analyze their genitalia. Since Sauter (1990), about 30 species, almost all European ones, have been newly combined from Gnophos Treitschke, 1825 to Charissa (Parsons et al. 1999). Currently, the genus is under revision by the authors of the present paper, and the genus name is under protection according to § 23.9.3. ICZN (Erlacher & Erlacher 2017).